A method for preparing high-performance antimony-based negative electrode material

By using water-soluble antimony salt, sodium tungstate and composite surfactant in lithium-ion batteries, an antimony-based negative electrode material with a white ear structure is formed, which solves the problem of volume expansion of antimony-based material during charge and discharge cycles, and improves electrochemical performance and cycle stability.

CN119284959BActive Publication Date: 2025-04-29HUNAN LOUDI HUAXING ANTIMONY IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411836410.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-29
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Antimony and its compounds expand severely during the charging and discharging cycle of lithium-ion batteries, resulting in cracking and crushing, making it difficult to meet the needs of high-performance electric vehicles and drones.

Method used

The antimony-based negative electrode material with a white fungus structure is formed by reacting water-soluble antimony salt, sodium tungstate and composite surfactant in a mixed solvent of anhydrous ethanol and deionized water by regulating the micromorphology of the product.

Benefits of technology

By exposing more active sites, this method promotes electron transfer and electrolyte penetration, inhibits volume expansion during charge and discharge, and improves cyclic stability and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284959B_ABST
    Figure CN119284959B_ABST
Patent Text Reader

Abstract

The invention relates to the field of negative electrode materials, and in particular to a method for preparing a high-performance antimony-based negative electrode material. A water-soluble antimony salt, sodium tungstate and a composite surfactant are added to a mixed solvent consisting of anhydrous ethanol and deionized water, stirred and mixed, sealed and heated to 120-140°C for reaction for 24-96 hours, filtered after returning to room temperature, and the precipitate is collected, washed and dried to obtain an antimony-based negative electrode material with a tremella-like structure. The antimony-based negative electrode material with a tremella-like structure is obtained by adding a composite surfactant and regulating the microscopic morphology of the generated product. The tremella-like structure exposes more active sites for lithium ion insertion / extraction, promotes electron transfer and electrolyte penetration, has a certain inhibitory effect on the volume expansion generated during the charge and discharge cycle, improves the cycle stability, and helps to improve the electrochemical performance of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of negative electrode materials, and in particular to a method for preparing a high-performance antimony-based negative electrode material. Background Art

[0002] With the booming global economy, environmental pollution and energy shortages are becoming increasingly serious. Therefore, it is urgent to develop clean renewable energy and new secondary batteries. Compared with other energy storage systems, lithium-ion batteries have advantages such as higher operating voltage and longer cycle life. They are considered to be the most promising energy storage devices in the 21st century. However, due to their limited energy density, they cannot meet the demand, especially in the field of high-performance electric vehicles and drones. In addition, with the rapid development of power facilities, higher requirements are placed on the cycle stability of secondary batteries. Among them, the development of highly stable negative electrode materials is one of the important contents in the research and development of secondary batteries.

[0003] Antimony and its compounds, as negative electrode materials for lithium-ion batteries, experience significant volume expansion during the charge and discharge cycle, which can lead to severe cracking and crushing. How to improve their electrochemical properties to meet large-scale industrial applications has become a problem that needs to be solved urgently. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for preparing a high-performance antimony-based negative electrode material.

[0005] The technical solutions adopted are as follows:

[0006] A method for preparing a high-performance antimony-based negative electrode material is as follows:

[0007] Add water-soluble antimony salt, sodium tungstate and composite surfactant into a mixed solvent consisting of anhydrous ethanol and deionized water, stir and mix, seal and heat to 120-140°C for reaction for 24-96h, return to room temperature and filter, collect the precipitate, wash and dry to obtain an antimony-based negative electrode material with a Tremella-like structure;

[0008] The composite surfactant is composed of a quaternary ammonium salt type gemini surfactant and a nonionic surfactant;

[0009] The mass ratio of the quaternary ammonium salt type gemini surfactant and the nonionic surfactant is 1-10:1-10;

[0010] The structural formula of the quaternary ammonium salt type gemini surfactant is as follows:

[0011] ;

[0012] Wherein, R is any one of n-hexanol, n-heptanol, n-octanol, n-nonanol, and n-decanol;

[0013] The nonionic surfactant is any one of polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600, or a combination of two or more thereof.

[0014] Furthermore, the preparation method of the quaternary ammonium salt type gemini surfactant is as follows:

[0015] Under nitrogen protection, dimethylaminoalkyl alcohol and 1,4-dibromobutane are added to anhydrous ethanol, stirred and mixed, and then heated to reflux for reaction for 24-48 hours. After the reaction is completed, the crude product is concentrated under reduced pressure to obtain a crude product. The obtained crude product is dissolved in anhydrous ethanol, cooled to 0-5°C, petroleum ether is added dropwise for crystallization, stirred at this temperature for 1-10 hours, filtered, and the product is collected and dried.

[0016] Furthermore, the molar ratio of dimethylaminoalkyl alcohol to 1,4-dibromobutane is 2-2.1:1.

[0017] Furthermore, the water-soluble antimony salt is antimony chloride and / or antimony nitrate.

[0018] Furthermore, the dosage of the composite surfactant is 1-10% of the mass of the water-soluble antimony salt.

[0019] Beneficial effects of the present invention:

[0020] The invention provides a method for preparing a high-performance antimony-based negative electrode material. A composite surfactant consisting of a quaternary ammonium salt-type gemini surfactant and a nonionic surfactant is added to adjust the microscopic morphology of a generated product, namely antimony tungstate, to obtain an antimony-based negative electrode material with a tremella-like structure. The tremella-like structure exposes more active sites for lithium ion embedding / ejection, promotes electron transfer and electrolyte penetration, has a certain inhibitory effect on volume expansion generated during charge and discharge cycles, improves cycle stability, and helps to improve the electrochemical performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM photo of the antimony-based negative electrode material prepared in Example 1;

[0022] Figure 2 This is a SEM photo of the antimony-based negative electrode material prepared in Comparative Example 1;

[0023] Figure 3 This is a SEM photo of the antimony-based negative electrode material prepared in Comparative Example 2;

[0024] Figure 4 This is a SEM photo of the antimony-based negative electrode material prepared in Comparative Example 3;

[0025] Figure 5 This is a SEM photograph of the antimony-based negative electrode material prepared in Comparative Example 4. DETAILED DESCRIPTION

[0026] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0027] Embodiment 1:

[0028] This embodiment provides a method for preparing a high-performance antimony-based negative electrode material:

[0029] 45.6g of antimony chloride, 29.4g of sodium tungstate, 1g of quaternary ammonium salt type gemini surfactant and 1g of polyethylene glycol 200 were added to a mixed solvent consisting of 200ml of anhydrous ethanol and 800ml of deionized water, stirred for 10min to mix, and then transferred to a hydrothermal reactor with a tetrafluoroethylene liner, sealed and heated to 120°C for 48h. After the reaction, the reaction was restored to room temperature, filtered, and the precipitate was collected, washed with anhydrous ethanol and deionized water, and then dried to obtain an antimony-based negative electrode material. In order to study the morphology and microstructure of the prepared antimony-based negative electrode material, it was observed by scanning electron microscopy, which showed that it had a tremella-like structure. For details, see Figure 1 .

[0030] Among them, the structural formula of the quaternary ammonium salt type gemini surfactant is as follows:

[0031] ;

[0032] The preparation method of the above-mentioned quaternary ammonium salt type gemini surfactant is as follows:

[0033] Under nitrogen protection, 3.55g (0.0205mol) 8-dimethylamino-1-octanol and 2.16g (0.01mol) 1,4-dibromobutane were added to 50ml anhydrous ethanol, stirred and mixed, and then heated to reflux for reaction for 48h. After the reaction, the ethanol was removed under reduced pressure and concentrated to obtain a crude product. The crude product was properly heated and dissolved with 10ml anhydrous ethanol, cooled to 0-5℃, and 100ml petroleum ether was added dropwise for crystallization. After stirring at this temperature for 8h, the product was filtered and collected and dried.

[0034] Embodiment 2:

[0035] This embodiment provides a method for preparing a high-performance antimony-based negative electrode material:

[0036] 45.6g of antimony chloride, 29.4g of sodium tungstate, 1g of quaternary ammonium salt type gemini surfactant and 1g of polyethylene glycol 200 were added to a mixed solvent consisting of 200ml of anhydrous ethanol and 800ml of deionized water, stirred for 10min to mix, and then transferred to a hydrothermal reactor with a tetrafluoroethylene liner, sealed and heated to 125°C for 48h. After the reaction, the room temperature was restored, filtered, and the precipitate was collected, washed thoroughly with anhydrous ethanol and deionized water, and then dried to obtain an antimony-based negative electrode material. Observation by scanning electron microscopy showed that it had a tremella-like structure.

[0037] The structure and preparation method of the quaternary ammonium salt type gemini surfactant are the same as those in Example 1.

[0038] Embodiment 3:

[0039] This embodiment provides a method for preparing a high-performance antimony-based negative electrode material:

[0040] 45.6g of antimony chloride, 29.4g of sodium tungstate, 1g of quaternary ammonium salt type gemini surfactant and 1g of polyethylene glycol 200 were added to a mixed solvent consisting of 200ml of anhydrous ethanol and 800ml of deionized water, stirred for 10min to mix, and then transferred to a hydrothermal reactor with a tetrafluoroethylene liner, sealed and heated to 130°C for 48h. After the reaction, the room temperature was restored, filtered, and the precipitate was collected, washed thoroughly with anhydrous ethanol and deionized water, and then dried to obtain an antimony-based negative electrode material. Observation by scanning electron microscopy showed that it had a tremella-like structure.

[0041] The structure and preparation method of the quaternary ammonium salt type gemini surfactant are the same as those in Example 1.

[0042] Embodiment 4:

[0043] This embodiment provides a method for preparing a high-performance antimony-based negative electrode material:

[0044] 45.6g of antimony chloride, 29.4g of sodium tungstate, 1g of quaternary ammonium salt type gemini surfactant and 1g of polyethylene glycol 200 were added to a mixed solvent consisting of 200ml of anhydrous ethanol and 800ml of deionized water, stirred for 10min to mix, and then transferred to a hydrothermal reactor with a tetrafluoroethylene liner, sealed and heated to 135°C for 48h. After the reaction, the room temperature was restored, filtered, and the precipitate was collected, washed thoroughly with anhydrous ethanol and deionized water, and then dried to obtain an antimony-based negative electrode material. Observation using a scanning electron microscope showed that it had a tremella-like structure.

[0045] The structure and preparation method of the quaternary ammonium salt type gemini surfactant are the same as those in Example 1.

[0046] Embodiment 5:

[0047] This embodiment provides a method for preparing a high-performance antimony-based negative electrode material:

[0048] 6g of antimony chloride, 29.4g of sodium tungstate, 1g of quaternary ammonium salt type gemini surfactant and 1g of polyethylene glycol 200 were added to a mixed solvent consisting of 200ml of anhydrous ethanol and 800ml of deionized water, stirred for 10min to mix, and then transferred to a hydrothermal reactor with a tetrafluoroethylene liner, sealed and heated to 140°C for 48h. After the reaction, the room temperature was restored, filtered, and the precipitate was collected, washed thoroughly with anhydrous ethanol and deionized water, and then dried to obtain an antimony-based negative electrode material. Observation by scanning electron microscopy showed that it had a tremella-like structure.

[0049] The structure and preparation method of the quaternary ammonium salt type gemini surfactant are the same as those in Example 1.

[0050] Comparative Example 1:

[0051] The same as Example 1, except that no quaternary ammonium salt type Gemini surfactant and polyethylene glycol 200 were added. In order to study its morphology and microstructure, it was observed by scanning electron microscopy and showed that it was a nanosheet layered structure. Figure 2 .

[0052] Comparative Example 2:

[0053] The same as Example 1, except that no quaternary ammonium salt type gemini surfactant was added. In order to study its morphology and microstructure, it was observed by scanning electron microscope and showed that it was an irregular block structure. Figure 3 .

[0054] Comparative Example 3:

[0055] The same as Example 1, except that polyethylene glycol 200 was not added. In order to study its morphology and microstructure, it was observed by scanning electron microscopy and showed that it was a hybrid structure of nanosheets / nanorods. Figure 4 .

[0056] Comparative Example 4:

[0057] The same as Example 1, except that CTAB (cetyltrimethylammonium bromide) is used instead of the quaternary ammonium salt type gemini surfactant. In order to study its morphology and microstructure, it is observed by scanning electron microscopy and shows that it is a cluster structure. For details, see Figure 5 .

[0058] Performance Testing:

[0059] CR2025 button batteries were prepared in a glove box filled with argon. The negative electrode materials prepared in Examples 1-5 of the present invention and Comparative Examples 1-4 were mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce electrode materials. The synthesized slurry was applied on a copper foil with a thickness of 150 μm, placed in a vacuum oven, and dried at 110° C. for 12 h. The electrode was then punched into a circular sheet with a diameter of 12 mm and pressed with a small tablet press at a pressure of 10 MPa to enhance the contact between the material and the copper foil. Celgard 2300 membrane was used as the diaphragm, and pure lithium was used as the counter electrode. 1 mol of lithium hexafluorophosphate was dissolved in 1 L of a mixed organic solvent of diethyl carbonate (DEC) / ethylene carbonate (EC) / dimethyl carbonate (DMC) ( V (DEC): V (EC): V (DMC)=1:1:1) was used as the electrolyte, and the electrochemical performance was tested on the Blue Battery Test System. The cyclic voltammetry (CV) test was performed on the CH1600E electrochemical workstation with a voltage of 0.05-3.00 V and a current density of 1.0 A / g. The test results are shown in Table 1 below:

[0060] ;

[0061] As can be seen from Table 1 above, the negative electrode material prepared by the present invention has relatively excellent electrochemical performance;

[0062] By comparing Example 1 with Comparative Examples 1-4, it can be seen that the quaternary ammonium salt-type gemini surfactant and polyethylene glycol 200 in the present application are extremely important for the formation of the tremella-like structure of the antimony-based negative electrode material, and performance tests show that the structure has the best electrochemical performance.

[0063] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-performance antimony-based negative electrode material, characterized in that: The details are as follows: Add water-soluble antimony salt, sodium tungstate and composite surfactant into a mixed solvent consisting of anhydrous ethanol and deionized water, stir and mix, seal and heat to 120-140°C for reaction for 24-96h, return to room temperature and filter, collect the precipitate, wash and dry to obtain an antimony-based negative electrode material with a Tremella-like structure; The composite surfactant is composed of a quaternary ammonium salt type gemini surfactant and a nonionic surfactant; The mass ratio of the quaternary ammonium salt type gemini surfactant and the nonionic surfactant is 1-10:1-10; The structural formula of the quaternary ammonium salt type gemini surfactant is as follows: ; Wherein, R is any one of n-hexanol, n-heptanol, n-octanol, n-nonanol, and n-decanol; The nonionic surfactant is any one of polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600, or a combination of two or more thereof.

2. The method for preparing a high-performance antimony-based negative electrode material according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt type gemini surfactant is as follows: Under nitrogen protection, dimethylaminoalkyl alcohol and 1,4-dibromobutane are added to anhydrous ethanol, stirred and mixed, and then heated to reflux for reaction for 24-48 hours. After the reaction is completed, the crude product is concentrated under reduced pressure to obtain a crude product. The obtained crude product is dissolved in anhydrous ethanol, cooled to 0-5°C, petroleum ether is added dropwise for crystallization, stirred at this temperature for 1-10 hours, filtered, and the product is collected and dried.

3. The method for preparing a high-performance antimony-based negative electrode material according to claim 2, characterized in that: The molar ratio of dimethylaminoalkyl alcohol to 1,4-dibromobutane is 2-2.1:

1.

4. The method for preparing a high-performance antimony-based negative electrode material according to claim 1, characterized in that: The water-soluble antimony salt is antimony chloride and / or antimony nitrate.

5. The method for preparing a high-performance antimony-based negative electrode material according to claim 1, characterized in that: The dosage of the composite surfactant is 1-10% of the mass of the water-soluble antimony salt.

Citation Information

Patent Citations

  • Method for preparation of flower-like nickel hydroxide electrode material from waste battery

    CN104409791A

  • Preparing method for flake-feature nano-composite metal oxide catalyst CeO2-Co3O4

    CN105597769A